Differential Impact of miR-21 on Pain and Associated Affective and Cognitive Behavior after Spared Nerve Injury in B7-H1 ko Mouse - Karl, Franziska; Grießhammer, Anne; Üçeyler, Nurcan; Sommer, Claudia (Frontiers in Molecular Neuroscience, 2017)
MicroRNAs (miRNAs) are increasingly recognized as regulators of immune and neuronal gene expression and are potential master switches in neuropathic pain pathophysiology. miR-21 is a promising candidate that may link the immune and the pain system. To investigate the pathophysiological role of miR-21 in neuropathic pain, we assessed mice deficient of B7 homolog 1 (B7-H1), a major inhibitor of inflammatory responses. In previous studies an upregulation of miR-21 had been shown in mouse lymphocytes. Young (8 weeks), middle-aged (6 months), and old (12 months) B7-H1 ko mice and wildtype littermates (WT) received a spared nerve injury (SNI). We assessed thermal withdrawal latencies and mechanical withdrawal thresholds. Further, we performed tests for anxiety-like and cognitive behavior. Quantitative real time PCR was used to determine miR-21 relative expression in peripheral nerves, and dorsal root ganglia (DRG) at distinct time points after SNI. We found mechanical hyposensitivity with increasing age of naïve B7-H1 ko mice. Young and middle-aged B7-H1 ko mice were more sensitive to mechanical stimuli compared to WT mice (young: p<0.01, middle-aged: p<0.05). Both genotypes developed mechanical and heat hypersensitivity (p<0.05) after SNI, without intergroup differences. No relevant differences were found after SNI in three tests for anxiety like behavior in B7-H1 ko and WT mice. Also, SNI had no effect on cognition. B7-H1 ko and WT mice showed a higher miR-21 expression (p<0.05) and invasion of macrophages and T cells in the injured nerve 7 days after SNI without intergroup differences. Our study reveals that increased miR-21 expression in peripheral nerves after SNI is associated with reduced mechanical and heat withdrawal thresholds. These results point to a role of miR-21 in the pathophysiology of neuropathic pain, while affective behavior and cognition seem to be spared. Contrary to expectations, B7-H1 ko mice did not show higher miR-21 expression than WT mice, thus, a B7-H1 knockout may be of limited relevance for the study of miR-21 related pain.